Gambaran Kepatuhan Diet Berdasarkan Karakteristik Pasien Gagal Ginjal Kronis Yang Menjalani Hemodialisa - Putri Gusmayanti, Inas; Saputra, Bayu; Lisa Indra, Rani (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2025)
Background : Chronic kidney failure that has reached the final stage (stage 5) requires kidney replacement therapy, one of which is hemodialysis. One of the crucial aspects in patient management is compliance with diet. Objewctive : to identify dietary compliance patterns based on the characteristics of chronic kidney failure patients undergoing hemodialysis. Method: This study is quantitative in nature with a descriptive survey design. The population in this study consisted of all patients undergoing hemodialysis in the hemodialysis room of Arifin Ahmad Regional General Hospital in Riau Province, totaling 79 samples using total sampling technique. The instrument used in this study was a diet compliance questionnaire. This study used univariate frequency distribution analysis. Result: the majority of patients in the young adult category group (19-39 years old) 46 people (58,3%), male 40 people (50,6%), the median hemodialysis period is 4 years, and the last high school education is 48 people (60,8%). The results of dietary compliance of the majority were obtained non-compliance of 46 people (57.0%) with characteristics, young adult age (19-39 years old) 23 people (30%), female gender 24 people (30,37%), hemodialysis period 1-4 years 24 people (30,37%), and high school education 26 people (32,91%). Conclusion: the majority of respondents are women aged 19-39 years old with the last high school education and undergoing hemodialysis for 1-5 years. From the total respondents, more people did not comply with the diet than those who obeyed. Dietary compliance is higher in patients with hemodialysis period ≤4 years, age 19-39 years, and high school education. There was no significant difference in compliance based on gender.